Neuromyelitis Optica with Negative AQP-4 Antibody: Poster Presentation - Case Report - Resident - Mokolensang Gabriella Olivia; Stevanus Paliliweu; Robby Tumewu (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Neuromyelitis Optica (NMO) or neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system that causes demyelination of the optic nerve and spinal cord. Approximately 75% of cases have antibodies against aquaporin 4 (AQP-4 Antibody). Case Illustration : A 42 years old male presented with progressing blurred vision in his right eye for 3 weeks. He described there was a black spot in his central vision which gradually enlarged to his peripheral vision, headache for 4 months, and transient tingling sensation and weakness on the left arm for 1 week. Positive RAPD in the right eye and signs of optic neuritis on funduscopy in Opthalmology examination. Campimetry examination revealed generalized depression in the right eye. The visual evoked potential (VEP) was consistent with right optic nerve demyelination. Spine MRI showed extensive transverse myelitis lesions >3 spinal cord hyperintensity on the level of C2-C6. However, the serum AQP-4 antibody was negative. The patient was treated with corticosteroid, and neuroprotector and was also being treated alongside the neurology department. Discussion : NMO is a rare autoimmune disease. NMO is characterized by segmented demyelination and inflammation of the spinal cord and the optic nerves which gives many ocular signs and symptoms like optic neuritis. A negative test result does not rule out the diagnosis of NMO. Brain and spine MRI plays an important role in diagnosing NMO. Treatment of NMO consists of corticosteroid and plasmapheresis or intravenous immunoglobulin. Conclusion : This case describes a diagnosis of NMO with a Negative AQP-4 antibody.